The Politics of Age : An Important Key to Understanding Power Relation in Indonesia Culture - Aswan, Aswan; Sultan, Iqbal; Sukri, Phil Sukri (Palakka : Media and Islamic Communication, 2024)
This article explores how age politics serve as a key factor in understanding power relations within Indonesian cultural society. Age-based stereotypes determine an individual’s position within organizational structures and social classes. Through the use of Critical Discourse Analysis, this study examines various daily communication interactions Through the use of Critical Discourse Analysis, this study examines various everyday communication interactions in families, communities, and institutions. Findings reveal that age politics systematically reinforce discriminatory practices, deeply rooted in social morality and institutional norms. Although there is a strong tendency to respect seniority, this dynamic is beginning to shift, especially in technology and creative fields, influenced by modernization and global values. Unfortunately, age-based stereotypes remain largely unchallenged in Indonesia.